PREDICTION OF FUEL TEMPERATURE OF AP1000 DUE TO THE FORMATION OF CRUD AND OXIDE LAYER - Muhammad Darwis Isnaini; Muhammad Subekti; Geni Rina Sunarya (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2017)
An analysis to predict the fuel temperature due to crud and oxide layer formed on the hot sub-channel cladding surface of AP1000 reactor has been performed. During reactor operation, the heat transfer and cooling process occur on the fuel cladding surface. During the heat exposure process, an oxide layer and crud are formed on the cladding surface. The decrease of heat transfer performance will increase the fuel and cladding temperatures. Therefore, the effect of fuel temperature increase during the heat exposure process has to be analyzed. The analysis was conducted for nominal power of 3400 MWt using COBRA-EN code, by varying the modular oxide thickness of 0, 20, 40, 60, 80, 100 and 120 mm, crud thickness of 0, 10 and 20 mm and black oxide thickness of 0, 10, 20, 30 and 40 mm. For full cycle hot sub-channel condition, the combination of crud thickness of 20 mm and modular oxide thickness of 115 mm give prediction of the peak fuel center line temperature and the peak cladding surface temperature of 1870.73°C and 609.40°C, respectively. However, the oxide layer is predicted only formed on hot sub-channel during BOC (about 40% of full cycle). The results show that the prediction of the peak fuel center line temperature and the peak cladding surface temperature are 1713.18°C and 451.87°C, respectively. Compared to the normal and fresh fuel conditions, the peak fuel center line temperature and the peak cladding surface temperature increase by 6.53% and 29.86%, respectively.Keywords: Fuel temperature, Crud, Oxide layer, COBRA-EN, AP1000 PREDIKSI TEMPERATUR BAHAN BAKAR AP1000 AKIBAT ADANYA BENTUKAN ENDAPAN DAN LAPISAN OKSIDA. Telah dilakukan penelitian untuk memprediksi temperatur bahan bakar akibat terbentuknya endapan dan lapisan oksida pada permukaan kelongsong sub kanal panas dari reaktor AP1000. Selama operasi reaktor, proses pemindahan kalor and pendinginan terjadi pada permukaan kelongsong. Selama proses pemaparan kalor, endapan dan lapisan oksida terbentuk pada permukaan kelongsong. Berkurangnya pemindahan kalor akan berakibat pada kenaikan temperatur bahan bakar dan kelongsong. Oleh karena itu, dampak kenaikan temperatur bahan bakar selama proses pemaparan kalor perlu dianalisis. Analisis dilakukan pada kondisi daya nominal sebesar 3400 MWt dengan menggunakan kode COBRA-EN, untuk variasi tebal lapisan oksida modular 0, 20, 40, 60, 80, 100 dan 120 mm, variasi tebal endapan 0, 10 dan 20 mm, dan variasi tebal lapisan oksida hitam 0, 10, 20, 30 dan 40 mm. Untuk kondisi sub kanal panas selama siklus penuh, kombinasi tebal 20 mm dan tebal lapisan oksida modular 115 mm memberikan prediksi temperatur puncak sumbu bahan bakar dan temperatur puncak permukaan kelongsong masing-masing sebesar 1870,73°C dan 609,40°C. Akan tetapi, lapisan oksida diprediksi hanya terjadi pada sub kanal panas selama awal siklus (sekitar 40% waktu satu siklus penuh). Hasil perhitungan menunjukkan bahwa prediksi temperatur puncak sumbu bahan bakar dan temperatur puncak permukaan kelongsong masing-masing sebesar 1713,18°C dan 609,40°C. Dibandingkan dengan temperatur bahan bakar pada kondisi segar dan normal, maka temperatur puncak sumbu bahan bakar dan temperatur puncak permukaan kelongsong mengalami kenaikan masing-masing sebesar 6,53% dan 29,86%. Kata kunci: Temperatur bahan bakar, endapan, lapisan oksida, COBRA-EN, AP1000.